Объяснение:
2Fe(OH)3 + 3H2SO4 = Fe2(SO4)3 + 6H2O
2Fe(OH)3 + 6H(+) + 3SO4(2-) = 2Fe(3+) + 3SO4(2-) + 6H2O
2Fe(OH)3 + 6H(+) = 2Fe(3+) + 6H2O
Fe(OH)3 + 3H(+) = Fe(3+) + 3H2O
Mg(NO3)2 + 2KOH = Mg(OH)2 + 2KNO3↓
Mg(2+) + 2NO3(-) + 2K(+) + 2OH(-) = Mg(OH)2↓ + 2K(+) + 2NO3(-)
Mg(2+) + 2OH(-) = Mg(OH)2↓
K2CO3 + BaCl2 = 2KCl + BaCO3↓
2K(+) + CO3(2-) + Ba(2+) + 2Cl(-) = 2K(+) + 2Cl(-)+ BaCO3↓
Ba(2+) + CO3(2-) = BaCO3↓
BaCO3 + 2HCl = BaCl2 + CO2↑ + H2O
BaCO3 + 2H(+) + 2Cl(-)= Ba(2+) + 2Cl(-)+ CO2↑ + H2O
BaCO3 + 2H(+) = Ba(2+) + CO2↑ + H2O
на катоде выделился H2 ,на аноде Cl2
найдем ню(Сl2)= 5,6/22,4=0,25 моль,
по ур-ию ню(H2)=0,25моль,V(H2)=5,6 л
ню(NaOH)=0,25*2=0,5 моль
m(NaOH)=0,5моль*40г/моль=20г